Sustained MK-801 induced deficit in a novel probabilistic reversal learning task - Latuske, Patrick; von Heimendahl, Moritz; Deiana, Serena; Wotjak, Carsten T.; du Hoffmann, Johann (Frontiers in Pharmacology, 2022)
Cognitive flexibility, the ability to adapt to unexpected changes, is critical for healthy environmental and social interactions and thus to everyday functioning. In neuropsychiatric disease, cognitive flexibility is often impaired and treatment options are lacking. Probabilistic reversal learning (PRL) is commonly used to measure cognitive flexibility in rodents and humans. In PRL tasks, subjects must sample choice options and, from probabilistic feedback, find the currently best choice which then changes without warning. However, in rodent, pharmacological models of human cognitive impairment tend to disrupt only the first (or few) of several contingency reversals, making quantitative assessment of behavioural effects difficult. To address this limitation, we developed a novel rat PRL where reversals occur at relatively long intervals in time that demonstrates increased sensitivity to the non-competitive NMDA receptor antagonist MK-801. Here, we quantitively compare behavior in time-based PRL and a widely used task where reversals occur based on choice behavior. In time-based PRL, MK-801 induced sustained reversal learning deficits both in time and across reversal blocks but, at the same dose, only transient weak effects in performance-based PRL. Moreover, time-based PRL yielded better estimates of behavior and reinforcement learning model parameters which opens meaningful pharmacological windows to efficiently test and develop novel drugs preclinically with the goal of improving cognitive impairment in human patients.